2020
DOI: 10.1088/1755-1315/575/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the damage rate of prehistoric cave images: a case study in the Maros-Pangkep karst area South Sulawesi Province, Indonesia

Abstract: Damage to prehistoric cave drawings, like other cultural objects, is inevitable. This claim was widely accepted among researchers and observers of prehistoric culture in Indonesia. Even more so for images in karst caves with a medium for painting in the form of limestone surfaces that have dynamic properties. The life cycle of this rock type is influenced by natural processes, mainly by water factors such as dissolution and sedimentation. In addition, the sun, temperature fluctuations, and wind also accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…8 ). Here, time-lapse photography conducted since October 2018 has identified an active exfoliation hot-spot within a rock art panel dominated by inactive spall-patches 3 . The width of the most active spall-patch under investigation has doubled from ~2.5 cm to ~5 cm between October 2018 and June 2021.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…8 ). Here, time-lapse photography conducted since October 2018 has identified an active exfoliation hot-spot within a rock art panel dominated by inactive spall-patches 3 . The width of the most active spall-patch under investigation has doubled from ~2.5 cm to ~5 cm between October 2018 and June 2021.…”
Section: Resultsmentioning
confidence: 95%
“…Knowledge of the long-term history of the Maros-Pangkep rock art loss is essential to put the observed damage into context and evaluate potential causes. A recent conservation study of 340 rock art images in five sample caves showed that 93% are damaged 3 . Twelve types of physical, chemical and biological causes have been identified, with exfoliation (89%) and algal growth (31%) dominant 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations